The effectiveness of benzydamine hydrochloride gargle versus throat spray in pain control post tonsillectomy patient : a randomized controlled trial - Arepen, Siti Asmat Md (2017)
Introduction: Post tonsillectomy pain is an undesirable complication for the patient which can disturb patient emotion and daily activity. There are many studies conducted to improve pain in post tonsillectomy patient. Several different surgical techniques and medications were introduced to find the best treatment for it. In this study, we focus more on local analgesia using different methods of delivery. Objective :To compare the effectiveness of different mode of delivery gargle versus throat spray of Benzydamine Hydrochloride in post tonsillectomy pain control Methodology: This study included 92 patients age from 13 to 40 who underwent tonsillectomy with or without adenotonsillectomy. They were randomly divided into two group with 46 patients in each group labeled as gargle group and spray group. Pain score using Visual Analogue Score (VAS) was assessed for both group at least 6-hour post operation for baseline pain score followed by Day 1, 4 and 7. Result :In the analysis of between group difference, result for the pain score using VAS showed significant difference between gargle and throat spray) (p< 0.001). Conclusion: Using throat spray as a method to deliver local analgesia give benefit in pain control for post tonsillectomy patients.